Knowledge of Childhood Autism and Challenges of Management among Medical Doctors in Kaduna State, Northwest Nigeria. (23rd March 2015) - Eseigbe, E. E.; Nuhu, F. T.; Sheikh, T. L.; Eseigbe, P.; Sanni, K. A.; Olisah, V. O.
Abstract : Autism is a neurodevelopmental disorder with serious implications in childhood. There is a significant gap in the identification and provision of health and social services for autism in Africa. The knowledge of autism among health care providers and identifying challenges associated with its management could facilitate bridging the gap and ensuring better outcomes. A self-administered tool, the Knowledge about Childhood Autism among Health Workers (KCAHW) questionnaire, was used in assessing knowledge of autism among 175 medical doctors (participants) attending an annual scientific meeting in northwest Nigeria. Other parameters assessed were sociodemographic and professional characteristics of the participants and challenges encountered in the management of autism. Out of 175 questionnaires distributed, 167 (95.4%) were returned. Good knowledge (KCAHW score ≥15) was significantly associated with being a paediatrician or psychiatrist and practicing in a tertiary health facility (P < 0.05 ), while poor knowledge (KCAHW score <15) was significant among general practitioners (P < 0.05 ). The highest knowledge gap was associated with onset of autism and its comorbidities (KCAHW Domain 4) while the least was concerning communication impairments (KCAHW Domain 2). Major challenges encountered in autism management were dearth of specialist services, cost of evaluation, and poor caregiver perspectives of autism.